Leaping-In And Leaping-Ahead: An Exploration Of Heidegger’s Notion Of Solicitude (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This paper looks at Heidegger's distinction between leaping-in-solicitude (einspringende Fuersorge) and leaping-ahead-solicitude (vorspringende Fuersorge) and its importance for the therapeutic relationship. In Part Two, two examples of leaping-in-solicitude are given from the setting of Forensic Psychiatry. In Part Three, an example is given from the same setting but in the author's role as an Art Psychotherapist. Conclusions are then made for therapeutic practice.
Keywords: Being and being; caring; remembering and forgetting; solicitude; concern; leaping-in; leaping-ahead; forensic psychiatry; art psychotherapy.